Routine in vitro culture of P. falciparum gametocytes to evaluate novel transmission-blocking interventions. - Lamas,Oliveira Marques S (Nature Protocols, 2016)
The prevention of parasite transmission from the human host to the mosquito has been recognized as a vital tool for malaria eradication campaigns. However, transmission-blocking antimalarial drug and/or vaccine discovery and development is currently hampered by the expense and difficulty of producing mature Plasmodium falciparum gametocytes in vitro-the parasite stage responsible for mosquito infection. Current protocols for P. falciparum gametocyte culture usually require complex parasite synchronization and addition of stimulating and/or inhibitory factors, and they may not have demonstrated the essential property of mosquito infectivity. This protocol details all the steps required for reliable P. falciparum gametocyte production and highlights common factors that influence culture success. The protocol can be completed in 15 d, and particular emphasis is placed upon operating a gametocyte culture facility on a continuous cycle. In addition, we show how functionally viable gametocytes can be used to evaluate transmission-blocking drugs both in a field setting and at high throughput (HTP) for drug discovery.